Dampak Putusan Mahkamah Konstitusi Nomor 135/Puu-Xxii/2024 Terhadap Pemisahan Pemilu Nasional dan Daerah Mulai 2019 - Mulawarman; Pasha Azzahra Febriana; Siska Inayah; Dea Rizky Amalia; Risma Asriani Aziz Genisa (Universitas Halu Oleo (UHO), 2026)
This study aims to critically examine the impact and practicality of the Constitutional Court's decision Number: 135/PPU-XXII/2004 in separating national and regional elections, and assess its contribution to strengthening Indonesia's democratic governance in the future. The research method used is a type of qualitative research with a descriptive approach to analysis, data obtained through primary data by conducting direct interviews with informants and secondary data by collecting various literature, from books, journals that are in accordance with the author's research. The results of this study show that the simultaneous elections in 2019 and 2024 combined for one day of voting between national elections and local elections pose a technical and administrative burden for election organizers and reduce the quality of voter rationality and weaken the space for political deletion, especially at the regional level. This study concludes that the separation of national and regional elections provides benefits by focusing on voters, as well as easing the workload of organizers so that they are able to produce election results through a quality democratic process even though the cost burden is greater.